Perceptions of professional drug treatment staff in England about client barriers to narcotics anonymous attendance. (June 2015) - Day, Ed; Wall, Rosemary; Chohan, Gagandeep; Seddon, Jennifer
Abstract A growing body of research evidence shows that Twelve Step Group (TSG) attendance confers a consistent moderate beneficial effect on substance use. Clinicians potentially represent a major referral pathway to TSG. This qualitative study aimed to explore staff perceptions of the barriers to Narcotics Anonymous (NA) group attendance in a population receiving drug treatment, and potential strategies to increase attendance. A cross-sectional survey of substance misuse treatment professionals was conducted between January and April 2012 in Birmingham, England. Fifty-eight members of staff working within statutory community drug treatment teams were interviewed using qualitative research methods. The overarching themes within the staff accounts are described and the importance of these themes explored. Perceived objections to core elements of the 12 step programme (religious nature of the programme, powerlessness, surrender, desire to stop using drugs) were major obstacles to recommending NA attendance. However, a perception that the client would object to any form of group process, and concerns about risk both to the client and the TSG members were also important. Increased education about TSG practices and procedures was a commonly cited strategy for increasing levels of TSG referral, and in particular ensuring that clinicians attend open meetings themselves. An increased understanding and familiarity with the process and principles of TSGs may be necessary to increase promotion of TSG within drug treatment services in line with recent national policy promoting recovery from drug use.